Temporal and spatial variation in C, N, S and trace element contents in the leaves of Quercus ilex within the urban area of Naples. - Alfani, a; Baldantoni, D.; Maisto, G.; Bartoli, G.; Virzo De Santo, A. (Environmental pollution (Barking, Essex : 1987), 2000)
This paper presents a comparative analysis of the concentrations of C, N and S and several trace elements (Fe, Mn, Na, Zn, Cu, V, Pb, Ni, Cr, Cd) in leaves of Quercus ilex, an evergreen oak, collected in the urban area of Naples in 1989 and 1996. The samplings were carried out from 25 urban sites (roads with different traffic flows as well as urban and suburban parks) and from two remote areas as controls. Relative to 1989, the values measured in 1996 denote a strong decrement of S, Fe, Na, Pb, and Cr, with the exception of S in control sites. By contrast, C, N and Cd contents were higher in 1996 than in 1989. Cu and Ni showed a conspicuous increment in control sites as well as in urban sites facing the sea and in the parks, while in all the other urban sites these elements decreased remarkably. No significant difference was found in the leaf contents of Mn, Zn and V measured in 1989 relative to 1996. Both in 1989 and 1996 the contents of N, S, Fe, Na, Cu, Pb, V, Ni, Cr and Cd were significantly higher in leaves from urban sites than in the controls, reflecting the high degree of contamination of the urban area. Concentration factors expressed as the ratio of road/control values for most of the elements were still very high in leaves collected in 1996, though remarkably lower than in 1989.
The following values have no corresponding Zotero field: accession-num: 15092919
Keywords: air pollution biomonitoring; leaf elemental analysis; no x; so 2; Trace Elements

Temporal and spatial variation in C, N, S and trace element contents in the leaves of Quercus ilex within the urban area of Naples. - Alfani, a; Baldantoni, D; Maisto, G; Bartoli, G; Virzo de Santo, A (Environmental pollution (Barking, Essex : 1987), 2000)
This paper presents a comparative analysis of the concentrations of C, N and S and several trace elements (Fe, Mn, Na, Zn, Cu, V, Pb, Ni, Cr, Cd) in leaves of Quercus ilex, an evergreen oak, collected in the urban area of Naples in 1989 and 1996. The samplings were carried out from 25 urban sites (roads with different traffic flows as well as urban and suburban parks) and from two remote areas as controls. Relative to 1989, the values measured in 1996 denote a strong decrement of S, Fe, Na, Pb, and Cr, with the exception of S in control sites. By contrast, C, N and Cd contents were higher in 1996 than in 1989. Cu and Ni showed a conspicuous increment in control sites as well as in urban sites facing the sea and in the parks, while in all the other urban sites these elements decreased remarkably. No significant difference was found in the leaf contents of Mn, Zn and V measured in 1989 relative to 1996. Both in 1989 and 1996 the contents of N, S, Fe, Na, Cu, Pb, V, Ni, Cr and Cd were significantly higher in leaves from urban sites than in the controls, reflecting the high degree of contamination of the urban area. Concentration factors expressed as the ratio of road/control values for most of the elements were still very high in leaves collected in 1996, though remarkably lower than in 1989.
Keywords: air pollution biomonitoring; leaf elemental analysis; no x; so 2; Trace Elements